Predictive impact of MGMT promoter methylation in glioblastoma of the elderly - Reifenberger, Guido; Wick, Wolfgang (International journal of cancer, 2012)
O6-methylguanine-DNA-methyltransferase (MGMT) promoter methylation identifies a subpopulation of glioblastoma patients with more favorable prognosis and predicts a benefit from alkylating agent chemotherapy (CT). Little is known about its prevalence and clinical significance in older glioblastoma patients. We studied 233 glioblastoma patients aged 70 years or more (144 males, 89 females, median age: 74 years, range: 70.0-86.6 years), who were prospectively enrolled in the German Glioma Network, for MGMT promoter methylation by methylation-specific PCR (MSP) in all patients and DNA pyrosequencing in 166 patients. MGMT data were correlated with patient outcome. Median progression-free survival (PFS) was 4.8 months (95% CI: 4.3-5.3) and median overall survival (OS) was 7.7 months (95% CI: 6.3-9.0). MGMT promoter methylation was detected by MSP in 134 patients (57.5%). For the whole cohort, PFS was 5.2 versus 4.7 months (p = 0.207) and OS was 8.4 versus 6.4 months (p = 0.031) in patients with versus without MGMT promoter methylation. Patients with MGMT methylated tumors had longer PFS when treated with radiotherapy (RT) plus CT or CT alone compared to patients treated with RT alone. Patients with MGMT unmethylated tumors appeared to derive no survival benefit from CT, regardless of whether given at diagnosis together with RT or as a salvage treatment. Patients treated with RT plus CT or CT alone demonstrated longer OS when pyrosequencing revealed >25% MGMT methylated alleles. Taken together, MGMT promoter methylation may be a useful biomarker to stratify elderly glioblastoma patients for treatment with versus without alkylating agent CT.
First published: 03 December 2011
Gesehen am 04.05.2018